Understanding Politics: Ideas, Institutions, and Issues, 13th Edition - Thomas M. Magstadt (Cengage Learning, 2020)
"Politics is a gateway to a broader and better understanding of human nature, society and the world"" is the inspiration behind Magstadt's UNDERSTANDING POLITICS: IDEAS, INSTITUTIONS, AND ISSUES. Thoroughly updated, the 13th Edition provides in-depth coverage of contemporary political issues and places them in the context of more enduring underlying questions. It analyzes three fundamental premises: Politics is a pervasive force in modern society; government is too important to be left in the hands of a few; and the right to participate in public life is a precious thing unique to republics. Coverage includes key concepts like democracy, ideology, citizenship, voting behavior, public policy, leadership and foreign policy, along with analysis of the Trump presidency, social media in politics, Russian interference in Western elections, Brexit, the rise of China as partner and rival and more. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.